2018
DOI: 10.1155/2018/3061974
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenMnSODVal16Ala Polymorphism and Cancer Risk: Evidence from 33,098 Cases and 37,831 Controls

Abstract: Manganese superoxide dismutase (MnSOD) plays a critical role in the defense against reactive oxygen species. The association between MnSOD Val16Ala polymorphism and cancer risk has been widely studied, but the results are contradictory. To obtain more precision on the association, we performed the current meta-analysis with 33,098 cases and 37,831 controls from 88 studies retrieved from PubMed, Embase, Chinese National Knowledge Infrastructure (CNKI), and Wanfang databases. Pooled odds ratios (ORs) and 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 131 publications
1
9
0
Order By: Relevance
“…Overall results indicated that SOD Val16Ala polymorphism is correlated with increased urological cancer susceptibility, especially for prostate cancer, which is consistent with previous findings. [14,33,55]. In stratified analysis by race, we observed similar findings in Caucasians and mixed populations, but not in Asians and Africans.…”
Section: Discussionsupporting
confidence: 69%
“…Overall results indicated that SOD Val16Ala polymorphism is correlated with increased urological cancer susceptibility, especially for prostate cancer, which is consistent with previous findings. [14,33,55]. In stratified analysis by race, we observed similar findings in Caucasians and mixed populations, but not in Asians and Africans.…”
Section: Discussionsupporting
confidence: 69%
“…However, Wang's 2018 study showed that MnSOD gene polymorphisms were associated with cancer as a whole (breast, prostate, lung, bladder, pancreatic cancer, colorectal, ovarium, hepatocellular carcinoma, and non-Hodgkin's lymphoma) and subgroup analysis found an association between MnSOD gene polymorphisms and prostate cancer and no association with breast cancer. However, previous metanalytic studies by Kang in 2015 and Bang in 2008 showed that there was no relationship between MnSOD gene polymorphisms and overall cancer incidence [8], [9], [10].…”
Section: Resultsmentioning
confidence: 99%
“…MnSOD protein is an antioxidant enzyme that participates in the mitochondrial respiration by detoxifying the free radical superoxides [92]. In relation with the critical role of MnSOD in the defense against reactive oxygen species, it has been implicated in different diseases, such as type 2 diabetes, cardiovascular diseases, and cancer [93][94][95]. For instance, MnSOD overexpression originated a reduction of EV-associated PYGB protein, being EVs containing PYGB, a sensitive biomarker of cardiac injury [96].…”
Section: Manganese Superoxide Dismutase (Mnsod)mentioning
confidence: 99%